Time value of money in Islamic law of transactions : a brief comparison with conventional practices - Abd Daim, Mohamed Vall (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2010)
Time value of money is the backbone of the conventional economics. It is considered as a subject matter of sale in the conventional system of economics. However, the view of Islamic economics seems to be different. Although, time value of money has been accepted in several cases of Islamic law of transactions as an essential factor of trade and business, it is completely ignored in some other cases. This duality of consideration makes it difficult to figure out the Islamic perception of time value of money. This study has attempted to clarify the ambiguity that exists in the consideration or the view of Islamic economics pertaining time value of money for finding a better understanding of this problem. The methodology used by the researcher is mainly an analytical study of the relevant literature of the topic. In this regard a survey of the old Islamic resources has been made. The researcher has purported to analyse and examine the Islamic literature concerning this issue and collect all relevant Islamic transactions in one compilation to unveil the vagueness associated with this matter and build a complete theory regarding it. The study of this subject has shown that time value of money is much interrelated with the prohibition of riba and interest in Islamic law of transactions. That is why the approach of time value of money in al-Shariah varies from one transaction to another such as, loan and sale. For example, Islamic law accepts the time value of money in sale and rejects it in loan. The permission of the increase of price in deferred payment sale and the reduction of price in forward sale (al-salam) deemed to be a sign for the application and acceptance of time value of money, whereas, the prohibition of interest in loans and debts gives an opposite impression about the acceptance of time value of money in Islamic law. This finding has been supported by many quotations from the eminent Muslim scholars. The duality of consideration of time value of money in Islamic law has its root in the prohibition of riba in al-Shariah. In this context, Islam allows profit in sales and prohibits interest in loans and debts. For the same reason, the application of time value of money in bay-al-Inah and tawarruq has been disputed by some scholars as they considered these transactions as same as loan while the scholars who considered these contracts as valid sales accepted the application of time value of money in them. It is also noticed that Islamic law emphasises the importance of time value of money in certain sanctions such as the prohibition of default of payment and the prohibition of riba-al-nasa. Based on the findings of this study it is recommended for the players in Islamic finance to avoid the application of controversial contracts such as bay-al-Inah and tawarruq or any other structure related to riba. The application of time value of money also should not reach the stage of exploitation of poor and needy when dealing with them in BBA or al-salam